(untitled) (Research, Society and Development, 2021)
Introduction: Over-the-counter Medicines (MIPs) were approved by health authorities to treat minor or self-limited symptoms, being marketed in self-service pharmacies/drugstores and dispensed without the presentation of a prescription. In this scenario, pharmaceutical care is integrated as a health provider tool and guidance on the correct and discriminated use of PIMs, as this article aims to synthesize evidence on the importance of pharmaceutical care in the use of PIMs, aiming at patient safety. Methods: Integrative review and narrative synthesis, having as a guiding question the existence of evidence on pharmaceutical care in the use of PIMs, presenting as outcomes the reduction of the indiscriminate use of PIMs through the guidelines inherent to pharmaceutical care and the reduction of health problems caused by misusing MIPs. The time frame was from 2011 to 2021. Studies published in the Cochrane Library, Epistemonikos, Health Evidence, Virtual Health Library and Google Scholar databases were searched. Results and discussion: studies show that the indiscriminate use of MIPs is extremely high, which can cause serious health problems and also highlight that information regarding the correct use of MIPs is essential, among the main risks caused by the indiscriminate use of MIPs. if the overload caused to the liver, kidneys and lungs; skin infections and stomach bleeding. Conclusion: There is evidence that pharmaceutical care improves adherence to drug therapy and reduces problems related to the indiscriminate use of PIMs, but due to their easy access, these drugs are still used on a large scale.